PENGARUH KOMPETENSI GURU DAN BUDAYA SEKOLAH TERHADAP KUALITAS PENDIDIKAN - Winarto, Bambang; Linda Dwi Khusnarini, Mey; Wahyu Damayanti, Nia; Indrawati, Mei (Al-ATHFAL: Jurnal Pendidikan Anak, 2023)
This research discusses the influence of teacher competency and school culture on the quality of education in Gugus Paud AH. Nasution, Probolinggo City. AH Early Childhood Cluster. AH Early Childhood Cluster. Nasution is a coordination platform for various PAUD institutions, such as TK, KB, SPS and TPA, which operate in Wonoasih District, Probolinggo City. This research utilizes a quantitative approach by applying statistical formulas for data analysis. The main aim of the research is to evaluate the impact of teacher competency and school culture on the quality of education through teacher performance in Gugus Paud AH. Nasution, Probolinggo City. From the research results, it was concluded that the influencing variables were the school culture variable on the quality of education, the teacher competency variable on teacher performance. Meanwhile, other variables have no influence, such as teacher competency variables on the quality of education, teacher performance variables on the quality of education, school culture variables on teacher performance, teacher competency variables on the quality of education through teacher performance and school culture variables on the quality of education through teacher performance. Keywords: Competence, Culture, Quality and Performance.